The Influence of Marketing Mix on Patient Decision-Making in Choosing Nur'aini General Hospital South Labuhan Batu - Trilia Mandasari; Arifah Devi Fitriani; Nuraini Nuraini (PROMOTOR, 2024)
Analysis of consumer behavior in health services is crucial in securing a company's sustainability. Amid intense competition, consumer perceptions about the quality of service at hospitals greatly influence their visiting decisions. This research focuses on the case study of Nur'aini General Hospital, which experienced a decline in patient visits from 2013 to 2016. The research method used a survey with 79 respondents from inpatients. The results show that the majority of respondents are adults, have secondary education, and most are women. Data is described in various variables such as service products, rates, service places, promotions, people involved, service processes, and physical facilities. The results of this research can help RSU Nur'aini improve marketing and service strategies to overcome the decline in the number of patient visits.